MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS LITERASI DIGITAL UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PESERTA DIDIK DI MADRASAH ALIYAH NEGERI BATANG JAWA TENGAH - Sahlan, Mohammad (Fakultas Agama Islam Universitas Islam Madura, 2024)
This research aims to increase student motivation and learning achievement using a project-based learning model based on digital literacy. This literacy ability is important in learning to improve students' critical, logical, and innovative thinking abilities. This research also aims to provide insight into improving students' literacy skills by using a project-based learning model. This research is Classroom Action Research. This research uses 2 stages, namely the initial or pre-cycle and the implementation stage which consists of 2 cycles. The subjects in this research were students of Class XII Madrasah Aliyah Negeri Batang. The data in this research was collected using observation, interview, and test techniques. This research uses data analysis developed by Miles, Huberman, and Saldana. With the research results, the project-based Learning Model based on digital literacy can increase students' motivation and learning achievement results. Students are also able to create and compile project assignments and publish them well.